2011
DOI: 10.1093/qjmed/hcr159
|View full text |Cite
|
Sign up to set email alerts
|

Is there anything good in uric acid?

Abstract: High uric acid (UA) levels can cause gout, urolithiasis and acute and chronic nephropathy, all of which are due to the deposit of urate crystals. There is also increasing evidence of relationships of hyperuricemia with other important disorders, including hypertension, chronic renal disease, metabolic syndrome and cardiovascular disease, as well as an increased mortality, although a causal relationship between these conditions has not been clearly established. On the other hand, low UA levels are not known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 82 publications
1
96
0
1
Order By: Relevance
“…High physiological UA levels in humans and higher primates have been hypothesized to be protective against oxidative stress [18, 19]. However, a series of well-grounded epidemiological studies have demonstrated the association between high serum UA levels and increased risk for a variety of diseases [20-23].…”
Section: Discussionmentioning
confidence: 99%
“…High physiological UA levels in humans and higher primates have been hypothesized to be protective against oxidative stress [18, 19]. However, a series of well-grounded epidemiological studies have demonstrated the association between high serum UA levels and increased risk for a variety of diseases [20-23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that hyperuricemia is linked not only to gout but also to other important disorders including hypertension, chronic kidney disease, cardiovascular disease, and metabolic syndrome [29]. Prior to considering a drug treatment for symptoms, adopting a progressive life style change such as healthier eating habits is considered important for the prevention and treatment of hyperuricemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, as Alvarez-Lario said (Alvarez, Macarrón, 2011), if UA was a waste or harmful product, it poorly explained why our kidneys recover 90% of filtered UA, instead of eliminating it. In fact, UA as a natural antioxidant plays an important role not only on induction of inflammatory response but also on anti-oxidative stress in peripheral and central tissue (Glantzounis et al, 2005).…”
Section: Introductionmentioning
confidence: 89%